Knowledge and Attitude of Iranian Dental Students and Specialists about Obstructive Sleep Apnea - Shafiei, Shervin; Sofi Mahmudi, Ahmad; Behnaz, Mohammad; Safiaghdam, Hannaneh; Sadr, Soroush (Journal of Dental School, 2021)
Objective Obstructive sleep apnea (OSA) is a relatively common sleep disorder, which leads to multiple sleep arousals and hypoxemia. We aimed to assess the knowledge and attitude of students and faculty members of ShahidBeheshti Dental School, Tehran, Iran about OSA. MethodsWe conducted a cross-sectional study on undergraduate and postgraduate students and faculty members of oral and maxillofacial (OMF) surgery, orthodontics, and oral medicine departments of ShahidBeheshti Dental School. The Obstructive Sleep Apnea Knowledge and Attitude (OSAKA) questionnaire was used to obtain information. We used the Chi-square, Kruskal Wallis, and Mann-Whitney U tests for statistical analysis. The data were analyzed by SPSS 22.0 (α <0.05). Results One hundred ninety-seven participants, including 43 dental students, 68 postgraduate students, and 64 faculty members filled out the questionnaire. The mean knowledge score among all participants was 10.69±3.133. Overall, OMF medicine and OMF surgeryfaculty members had significantly higher correct answer choices in the knowledge section than fifth and sixth-year dental students (P<0.001). There was no significant difference among other groups (P>0.05). About attitude, 91% of respondents reported that OSA is an important or extremely important disorder. However, only 10.2% and 16.9% felt confident about the ability to manage patients with OSA and identifying patients at risk of OSA, respectively. Overall, gender and educational level were correlated with the mean attitude score (P<0.05). Conclusion All participants had poor knowledge but a positive attitude towards OSA. This shows the necessity of better education about OSA.